2014
DOI: 10.1097/iop.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Dacryocystorhinostomy

Abstract: Endoscopic endonasal dacryocystorhinostomy is an effective treatment for nasolacrimal duct obstruction. An uncinectomy, septoplasty, and anterior middle turbinectomy contribute to the optimal clearance of the common canaliculus and ultimate surgical success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The reported rate of concomitant endoDCR and septoplasty for DNS is considerable, and ranges from 11.9 to 57%. [2,3,7,[13][14][15][16] In our series, the rate of concomitant endoDCR and septoplasty was 21.4% of patients who presented with NLDO. Our data showed that integrating an additional procedure (septoplasty) that was not performed for its original indication but rather for facilitating the main surgical intervention (endoDCR) yields results that are comparable with those for cases of endoDCR without septoplasty in terms of surgical success and complications.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The reported rate of concomitant endoDCR and septoplasty for DNS is considerable, and ranges from 11.9 to 57%. [2,3,7,[13][14][15][16] In our series, the rate of concomitant endoDCR and septoplasty was 21.4% of patients who presented with NLDO. Our data showed that integrating an additional procedure (septoplasty) that was not performed for its original indication but rather for facilitating the main surgical intervention (endoDCR) yields results that are comparable with those for cases of endoDCR without septoplasty in terms of surgical success and complications.…”
Section: Discussionmentioning
confidence: 52%
“…Figueira et al [2] reported a large series of 576 patients who underwent endoDCR, of whom 81 had concomitant endonasal procedures (septoplasty, turbinectomy, and polypectomy): the results were similar to those for the nonconcomitant procedures, but there was no reference to septoplasty alone. Fayet et al [3] demonstrated that higher rates of anterior middle turbinectomies and septoplasties performed during endonasal DCRs yielded higher rates of elimination of epiphora, but, again, septoplasty was not evaluated in isolation and it comprised only one quarter of all the endonasal procedures in that series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported rate of concomitant EDCR and septoplasty ranges from 11.9 to 57% [11,[24][25][26][27][28][29][30][31]. Per the literature, 39.7% of our cases were managed with a combined procedure.…”
Section: Discussionmentioning
confidence: 78%